La construcción de sociedades a través de plataformas web. - Calvopiña Recalde, Joseph Fabricio (2016)
The object of this article is to provide knowledge about network society, digital language, which promote new terms like communicology, cybercultures and social engineering, from the emergence of the web. These terms have spoken, understood and valued by netizens to understand and explain this complex universe that is called internet. In deep navigation internet web containers exist ranging from blogs, web pages, personal files found on social networks, web working environments and bank accounts; without forgetting the construction of virtual societies and providing information cybercultures massively to the network without any protection. This has caused most users and information are isolated and obsolete; but it does not mean they are eliminated, but became part of something called deep web. But why are there companies that are "isolated" on the web? Most users are unaware that these companies thanks to the rise develop information, and even sent archived on the web, massively intercepting all the information that users retain. Thus readers will understand that the web not only rotates through, social networking platforms recognized search, web pages, blogs, among others; but also there is another kind of virtual reality, which aims to encourage Internet users to understand the different terms that are appearing in conjunction with the web as well as virtual reality that every day is plasma.